Identification of common and specific fibrosis-related genes in three common chronic kidney diseases - Fu, Zhangning; Geng, Xiaodong; Liu, Chao; Shen, Wanjun; Dong, Zheyi; Sun, Guannan; Cai, Guangyan; Chen, Xiangmei; Hong, Quan (Renal failure, 2024)
Kidney fibrosis is the common final pathway of virtually all advanced forms of chronic kidney disease (CKD) including diabetic nephropathy (DN), IgA nephropathy (IgAN) and membranous nephropathy (MN), with complex mechanism. Comparative gene expression analysis among these types of CKD may shed light on its pathogenesis. Therefore, we conducted this study aiming at exploring the common and specific fibrosis-related genes involved in different types of CKD. Kidney biopsy specimens from patients with different types of CKD and normal control subjects were analyzed using the NanoString nCounter® Human Fibrosis V2 Panel. Genes differentially expressed in all fibrotic DN, IgAN and MN tissues compared to the normal controls were regarded as the common fibrosis-related genes in CKD, whereas genes exclusively differentially expressed in fibrotic DN, IgAN or MN samples were considered to be the specific genes related to fibrosis in DN, IgAN and MN respectively. Quantitative real-time PCR (qRT-PCR) was performed to validate the expression of the selected genes. Protein tyrosine phosphatase receptor type C (PTPRC), intercellular cell adhesion molecule-1 (ICAM1), vascular cell adhesion molecule-1 (VCAM1), interleukin 10 receptor alpha (IL10RA) and CC chemokine receptor 2 (CCR2) were identified as the potential common genes for kidney fibrosis in different types of CKD, while peroxisome proliferator-activated receptor alpha (PPARA), lactate oxidase (LOX), secreted phosphoprotein 1 (SPP1) were identified as the specific fibrosis-associated genes for DN, IgAN and MN respectively. qRT-PCR demonstrated that the expression levels of these selected genes were consistent with the NanoString analysis. There were both commonalities and differences in the mechanisms of fibrosis in different types of CKD, the commonalities might be used as the common therapeutic targets for kidney fibrosis in CKD, while the differences might be used as the diagnostic markers for DN, IgAN and MN respectively. Inflammation was highly relevant to the pathogenesis of fibrosis. This study provides further insight into the pathophysiology and treatment of fibrotic kidney disease.